Indonesia and Corona Pandemic: A Preliminary Study of Indonesian Muslim Responses on Covid-19 Pandemic - Sahrasad, Herdi; Dedy Tabrani; Qusthan A. H. Firdaus; Aris Arif Mundayat; Ti Aisyah; Al Chaidar (Hikmatuna : Journal for Integrative Islamic Studies, 2022)
This paper explains that in the case of the Corona(Covid-19) pandemic in Indonesia, many Muslim scholars and clerics differed in their response to the Corona outbreak, in which they give a different perspective that confuses people who do not really understand the Islamic teachings associated with this Corona outbreak. However, in the context of the responses of Muslimscholars toward Corona pandemic, it is recognized that the effort to overcome the Corona pandemic (Covid-19) through Medicine and Pharmacy is a human endeavor to strive for human safety in the world. This effort continues even though it is not easy. But many Muslim scholars and religious circles react emotionally and the leaders of these religious organizations will cause many followers or worshipers or members who then no longer believe or are pessimistic and lose confidence in certain sects. The government also cannot take advantage of this opportunity to make the direction of change more rational, more humane and civilized. Though this opportunity for change is available quite often in the span of productive power. In this context, many social scientists, especially anthropologists, have researched extraordinary drastic changes due to epidemics, pandemics or natural disasters, both due to human error and due to extreme pandemics and extreme natural changes. Indonesia as a developing country now is undergoing many unplanned drastic changes, and because of this, many social changes occur irregularly and without direction at all.